Physical oceanography during RV SENCKENBERG cruise SE202106-1 - Albinus, Michelle; Gerriets, Michaela; Geßner, Anna-Lena; Giebel, Helge-Ansgar; Thölen, Claudia; Wollschläger, Jochen; Badewien, Thomas Henry (PANGAEA, 2025)
Data presented here were collected during the cruise SE202106-1 with RV Senckenberg from Neuharlingersiel, Germany to Neuharlingersiel, Germany (28.06.2021 to 02.07.2021). In total, 34 vertical deep CTD-hauls were conducted. The CTD system used was a Sea-Bird Electronics Inc. SBE 19plus V2 probe (SN 7245). The CTD was attached to a SBE 55 Carousel Water Sampler (SN 5571979-0100) containing 6 4-liter Ocean Test Equipment Inc. bottles. The system was equipped with additonally an altimeter (Benthos, SN 4711), and an oxygen optode (Aandera, SN 1542). The sensors were pre-calibrated by the manufacturers. Data were recorded with the Seasave V 7.26.7.107 software and processed using the SeaBird SBE Data Processing V 7.26.7-b40. Data were converted, filtered, loop edited and bin averaged (size 0.25 m) and also visually checked. The ship position was derived from a trimble DGPS-system linked to the CTD data. The time zone is given in UTC. For more details on post-processing see the CTD processing report attached. Raw data on request.
Keywords: East Frisian Islands; North Sea; oceanography; Salinity; Temperature; tidal inlet; Wadden Sea